2015
DOI: 10.1126/scitranslmed.aac9816
|View full text |Cite
|
Sign up to set email alerts
|

The 20 S proteasome core, active within apoptotic exosome-like vesicles, induces autoantibody production and accelerates rejection

Abstract: Autoantibodies to components of apoptotic cells, such as anti-perlecan antibodies, contribute to rejection in organ transplant recipients. However, mechanisms of immunization to apoptotic components remain largely uncharacterized. We used large-scale proteomics, with validation by electron microscopy and biochemical methods, to compare the protein profiles of apoptotic bodies and apoptotic exosome-like vesicles, smaller extracellular vesicles released by endothelial cells downstream of caspase-3 activation. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
227
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(245 citation statements)
references
References 77 publications
16
227
1
1
Order By: Relevance
“…Serum-deprived endothelial cells release, besides apoptotic cell-derived vesicles, exosome-like EVs enriched in the LG3 fragment of the vascular extracellular matrix protein perlecam [90]. Repetitive injection of these endothelial-derived exosome-like EVs, unlike infusion of apoptotic cell vesicles from the same parent cells, triggers production of antibodies against the auto-antigen LG3 and aggravate vascular rejection in mice [90]. …”
Section: Alloantigen Presentation By Innate Immune Cellsmentioning
confidence: 99%
“…Serum-deprived endothelial cells release, besides apoptotic cell-derived vesicles, exosome-like EVs enriched in the LG3 fragment of the vascular extracellular matrix protein perlecam [90]. Repetitive injection of these endothelial-derived exosome-like EVs, unlike infusion of apoptotic cell vesicles from the same parent cells, triggers production of antibodies against the auto-antigen LG3 and aggravate vascular rejection in mice [90]. …”
Section: Alloantigen Presentation By Innate Immune Cellsmentioning
confidence: 99%
“…The release of proteasome in the blood plasma may be a result of membrane disruption. Some authors postulate that the release of active 20S proteasome is regulated [13]. In-vitro studies have shown that proteasome is released by injured endothelial cells, smooth muscle cells of the vessels and tubular epithelial cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors postulate that the release of active 20S proteasome is regulated [13]. In-vitro studies have shown that proteasome is released by injured endothelial cells, smooth muscle cells of the vessels and tubular epithelial cells [13]. A study by Ito et al [14] demonstrated that extracellular 20S proteasome is not only released from cells but also plays a functional role in physiological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptotic bodies are released by apoptotic cells and generally possess dimensions larger than 1000 nm123. However, it should be noted that these definitions are still subject to change, as larger exosomes (up to 250 nm) have been described, and apoptotic cells also release exosome-like vesicles34. Hence, the term EV is increasingly utilized, as it more liberally encompasses all vesicle types released by cells.…”
mentioning
confidence: 99%
“…EV subpopulations may contain active proteasome, organelles ( e.g . mitochondria), and may undergo post-translational modification in disease, such as citrullination in inflammatory arthritis41623252627. Furthermore, EVs are decorated with autoantibodies in autoimmune diseases such as systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA)162328, and different platelet stimuli were shown to trigger release of different EV subpopulations1824.…”
mentioning
confidence: 99%